도시의 냉각: 도쿄에게 헤이세이란 무엇이었을까? - 사다카네 히데유키(貞包英之)(릿쿄대학 사회학부 현대문화학과 (일본비평, 0(23), 2020)
헤이세이 도쿄는 버블 붕괴나 인구 구조의 고령화가 주요 원인으로 정체되어 왔다. 20세기 후반, 청년층이 새로운 구매력을 구성하면서 신주쿠나 시부야, 하라주쿠와 같은 새로운 번화가가 연이어 생겨났다. 그것이 도쿄의 현재를 확인하는 ‘도쿄론’의 번성을 불러오고, 또는 더욱 대중적인 수준에서는 잡지에서 다루는 거리 이야기의 활성화를 이끌어 왔다. 그러나 1990년대 후반 이후 디플레이션의 진행과 젊은층이 구매력을 잃으면서 도쿄는 더욱 ‘차가운’ 거리가 되었다. 물론 예외도 있었다. 과거 수도로서 도쿄를 지탱해 온 네이션의 틀에서 돌출된 힘이 도쿄의 지역을 바꿔 갔다. 그 원인 중 하나가 동아시아의 경제성장에 따라 구매력을 키운 이민자들이 오쿠보로 대표되는 에스닉 타운을 형성했기 때문이다. 또한 국가를 지탱하는 전후 가족의 틀에서 불거져 나온 사적인 구매력은, 아키하바라와 이케부쿠로로 대표되는 오타쿠 거리를 만들어 냈다. 이러한 변화는 중요하지만, 한편으로 그러한 변화는 부분적인 것으로 도쿄의 총체적인 틀을 바꾸지 못했다는 점에도 주목할 필요가 있다. 결과적으로 도쿄의 지역은 개개의 가로나 상자로 분단되어 다양한 군중들이 모일 수 있는 ‘공통의 장소’를 잃어버렸다. 그렇게 헤이세이 도쿄의 상황은, 코로나 이후 동아시아 여러 도시가 많든 적든 마주해야 할 문제와 이미 맞닥뜨리고 있는 것이다 In the Heisei era, Tokyo stagnated due mainly to the bursting of the bubble economy and the aging population. In the latter half of the 20th century, young people’s new purchasing power gave rise to new hotspots such as Shinjuku, Shibuya and Harajuku. This has led to the rise of “Studies on Tokyo (Tokyo-ron),” which confirms Tokyo’s present, or, at the more popular level, the rise of city narratives in information magazines. Since the latter half of the 1990s, however, Tokyo has become a “colder” city due to deflation and the loss of purchasing power by young people. Of course, there were some districts that were exceptions to the stagnation. A new force outside of the nation-state framework that once supported Tokyo as a capital city has been able to change the city. One of the factors is that immigrants who increased their purchasing power along with the growth of the East Asian economy formed ethnic towns represented by Okubo. On the other hand, the private buying power that has broken away from the post-war family framework that supported the nation created the streets of Otaku such as Akihabara and Ikebukuro. While these changes are important, it is also worth noting that, on the one hand, they were only partial and did not change the overall framework of Tokyo. As a result, the city of Tokyo is divided by individual streets and buildings as boxes, losing the “common ground” that bring together diverse crowds. This situation in Tokyo in the Heisei period is already facing the problems that many East Asian cities must face after COVID-19. KCI Citation Count: 1